Condemned bodies: experiences of homophobic hatred and violence in Pietermaritzburg, South Africa - Makhaye, Nandi (Sacrilegens, 2024)
The purpose of this paper is to present the thoughts, voices, and lived experiences of people who diverge from normative socio-cultural and religious prescriptions of gender and sexuality, namely black Izitabane[1] women located in Pietermaritzburg, South Africa. Through sharing these experiences, I hope to inspire deeper reflection and reconsideration of the role and presence of Izitabane women in African faith spaces and society. My reflections are framed by Queer Theology, asserting the importance of prioritizing the lived experiences of marginalized Izitabane people in scholarly discourse. This form of theology is particularly relevant and valuable for theologizing on Izitabane bodies, whose rights, experiences, perspectives, and existence are rejected as meaningless and denounced as unimportant. As a result, this methodology underscores the development of a theology from the margins in which the focus is placed on empowering the lives of black Izitabane women as essential points of reference for theological consideration.